ეპითეტები ანტიკურ ეპოსსა და რუსთაველის „ვეფხისტყაოსანში" - არველაძე ნათია (ლოგოსი, 2021)
The topic of our dissertation is "Epithet as an artistic mean of expression (Homer, Apollonius, Virgil)", where we studied the epithets presented in an- cient epic poetry (Homer, Apollonius, Virgil). We have made the appropriate classification of epithets. We also distinguished the common and distinctive features that are evident in terms of epithets in the works of the representatives of the ancient epic. We got interested in functions of the epithet expressed in the works by the three representatives of ancient epic poetry – Homer, Apollonius and Virgil, in whose work we believe that the epithet is one of the defining markers not only in creating an artistic effect, but also in developing the linguistic situation. Numerous works can be found about the relations between ancient epic po- etry and the poem “The Knight in the Panther’s Skin” by Shota Rustaveli, which highlight the issues of similarities and differences between the mentioned texts in different directions. Our interest in the interrelationships of epithets given by the three representatives of ancient epic poetry and Georgian epic writer Shota Rustaveli was caused by the rarity of the issue in Humanitarian literature, while a number of other approaches are elaborated and studied in depth. The urgency of the issue is also enhanced by the fact that the epithet by its functional purpose is one of the leading features of the epic genre and is the most active among the descriptors in epic works. We study the relations be- tween ancient epic poetry and Georgian epic poem “The Knight in the Panther’s Skin” by contrasting the similarities and differences of the epithets given in the studied texts. We have drawn a comparative line in two main directions: quanti- tative analysis – according to the frequency of epithets and qualitative analysis – according to their content. The following research makes an overview about the references that can be used as arguments to prove the relationships between Rustaveli and ancient epic poetry. The similarities between the epithets used in the epic poem by Rustaveli and in the ancient epic poetry ("Iliad", "Odyssey", "Argonautica", "Aeneid") give us the reason to believe that the ancient epic poetry, authored by Homer, Apollonius and Virgil, found an important reflection in the work by the Geor- gian epic writer Shota Rustaveli